A principal component analysis model-based predictive controller for controlling part warpage in plastic injection molding. Issue 6 (15th April 2015) - Zhang, Songtao; Dubay, Rickey; Charest, Meaghan
Highlights Quality measurement on injection molded parts are related to process parameter data. The data experimentation data is analyzed using statistical methods (PCA), (ICA) and (ANOVA). Models are constructed to predict a quality index based on data analysis results. A MPC scheme that allows for on-line quality control was developed using the models. The presented scheme is extendable to a variety of manufacturing processes.